COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN PARIWISATA BERBASIS SENI DAN BUDAYA DI DESA SINGAPADU TENGAH - Sarining, Komang (Jurnal Widya Publika, 2025)
Central Singapadu Village in Gianyar Regency is a designated tourism village, officially recognized through Gianyar Regent Decree No. 429/E-02/2017, for its preservation of local arts and culture. Guided by the Tri Hita Karana philosophy, the village promotes harmony between humans, nature, and the divine. While the development of art and culture-based tourism has adopted collaborative governance principles, its implementation remains suboptimal. Based on Ansell and Gash's (2008) Collaborative Governance Theory, initial collaboration was marked by face-to-face dialogue involving stakeholders such as the village government, tourism office, Pokdarwis (Tourism Awareness Group), and the community. The village government supports Pokdarwis through its roles as facilitator, educator, representative, and technical implementer. Despite shared commitments to community training and business development, challenges persist due to limited infrastructure, insufficient human resources, and lack of public awareness regarding Pokdarwis programs. Although initiatives such as traditional house villages, historical temples, and cultural activities are in place, their impact remains limited. Supporting factors include strong communication and cooperation between key actors, while inhibiting factors involve low community participation, limited funding, and inadequate human capital quality.